Rehabilitation of the patient with a partial maxillectomy defect with an interim hollow bulb obturator - C. B. Shanthana Lakshmi; Sushant A. Pai; Keerthi Ramachandra; S. A. Saadath Afzaa; Afreen Kouser (Wolters Kluwer Medknow Publications, 2022)
Maxillary obturator prosthesis is usually preferred for patient going through partial or total maxillectomy. The heavy weight of the obturator prosthesis is usually a major concern to the prosthodontist as it may cause inconvenience with masticatory function. The maxillary defect may be congenital or acquired; hence, the latter often leads to patients encountering an array of physical and psychological distress. Rehabilitation of such patients is often challenging due to the extent of the defect area. Achieving adequate retention is of utmost importance as it reinforces the obturator musculoskeletal coordination. The processing technique described in this case report is the lost salt technique using a single-step flasking procedure which was customized accordingly with heat-cure acrylic resin as stops on the flask to accommodate the closed hollow obturator prosthesis as a single unit. This article describes the management of a patient who had undergone partial hemimaxillectomy secondary to mucoepidermoid cell carcinoma rehabilitated with hollow obturator prosthesis.